2018
DOI: 10.30548/vascfail.2.1_20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cholesterol synthesis/absorption marker and vascular function in healthy subjects

Abstract: Recently, inhibition of absorbed cholesterol has been reported to reduce the recurrence of vascular events in patients with acute coronary syndrome. However, the effect of absorbed cholesterol on atherosclerosis in healthy subjects remains unclear. In the present study, we investigated the relationship between cholesterol synthesis and absorption biomarkers, and vascular elasticity or morphological changes in healthy subjects. Methods: Among 580 subjects who underwent a complete medical checkup between 2012 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The positively skewed distributions of Latho, Campe, and Sito concentrations of this study from Japan agreed with the results of Dayspring et al 12) from the US. Ishibashi et al 9) and Yoshida et al 14) also reported serum levels of Latho, Campe, and Sito in than in males. No significant interaction by sex was found in the association of the LDL-C/HDL-C ratio with Latho, Campe, or Sito.…”
Section: Distribution Of Serum Concentrations Of Non-cholesterol Sterolsmentioning
confidence: 92%
See 2 more Smart Citations
“…The positively skewed distributions of Latho, Campe, and Sito concentrations of this study from Japan agreed with the results of Dayspring et al 12) from the US. Ishibashi et al 9) and Yoshida et al 14) also reported serum levels of Latho, Campe, and Sito in than in males. No significant interaction by sex was found in the association of the LDL-C/HDL-C ratio with Latho, Campe, or Sito.…”
Section: Distribution Of Serum Concentrations Of Non-cholesterol Sterolsmentioning
confidence: 92%
“…Subjects with cardiovascular disease revealed higher levels of absorption biomarkers and lower levels of synthesis biomarkers than controls 4,5) . As reviewed previously 6) , many studies, but not all [7][8][9][10][11] , showed that increased levels of cholesterol absorption biomarkers were associated with increased risk of cardiovascular disease. Therefore, knowledge of an individual's cholesterol absorption and synthesis status could help in the stratification of cardiovascular risk.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation